An in vitro study to evaluate and compare the remineralizing potential among Casein Phosphopeptide-amorphous Calcium Phosphate (CPP-ACP) with fluoride and surface pre-reacted glass (S-PRG) fillers using quantitative analysis.: Comparison between two types of remineralizing agents. - Jabi, Shabista; Diwedi, Swati; Upadhyay, Vinod; Abdullah, Ahsan; Sarfaraj, Mohammad; Mishra, Ankur (International Journal of Dental Materials, 2021)
Background- Early treatment of white spot lesions is essential to prevent the progression of the lesion. Aim - To evaluate and compare the remineralizing potential of CPP-ACP with fluoride (Casein Phospho Peptide-Amorphous Calcium Phosphate) and S-PRG fillers (Surface Pre reacted glass fillers) using atomic absorption spectroscopy and colorimetric method. Materials and methods- Forty sound human premolars were used in this study. They were divided into two groups (A & B), consisting of 20 samples in each. White spot lesions (WSLs) were established on the window (4x4 mm2) created on the buccal surfaces of the samples. Samples in group A were treated with casein phosphopeptide amorphous calcium phosphate (CPP-ACP) with fluoride, those of group B were treated with S-PRG Fillers. The sample teeth were immersed in a demineralizing solution for 4 days. All the samples were subjected to loss of mineral content (wt %), i.e., calcium, using atomic absorption spectroscopy and phosphorus using the colorimetric method. Results- Statistical analysis was performed using one?way analysis of variance, Tukey’s and paired t?tests. Group A exhibited the highest remineralizing potential, followed by Group B. Statistically, a significant difference (p=0.001) was observed between the two groups. Conclusion- There was a significant difference in remineralizing potential of CPP-ACP with fluoride and S-PRG Fillers. CPP-ACP with fluoride appears to be an effective technique in the remineralization of white spot lesions.